1999
DOI: 10.1007/pl00002620
|View full text |Cite
|
Sign up to set email alerts
|

Water protection of wooden window joinery painted with low organic solvent content paints with known composition. Part 1. Results of inter-laboratory tests

Abstract: An investigation of the water protection capacity of modern paints with low organic solvent content was carried out as part of an European research project. The wider scope of the project was to establish the performance and durability of these new coatings applied to window joinery made from European softwood species. The aim of the moisture studies was to employ well-proven methods to determine the liquid water absorption of the coatings. A range of standard moisture permeability tests, carried out on coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…Constructions for outdoor purposes, such as house facades, are particularly exposed, and a coating is often used to limit the absorption of moisture. The moisture sorption behavior of coated wood has been studied extensively (Ahola et al 1999;Ekstedt 2002;Ekstedt 2003;Nejad and Cooper 2011;Van Meel et al 2011;Grüll et al 2013). However, studies on the subject are predominantly limited to the performance of the coating and do not address the relationship between coating performance and wood characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Constructions for outdoor purposes, such as house facades, are particularly exposed, and a coating is often used to limit the absorption of moisture. The moisture sorption behavior of coated wood has been studied extensively (Ahola et al 1999;Ekstedt 2002;Ekstedt 2003;Nejad and Cooper 2011;Van Meel et al 2011;Grüll et al 2013). However, studies on the subject are predominantly limited to the performance of the coating and do not address the relationship between coating performance and wood characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies of water transport through coating layers one investigated the average moisture content (MC) in bulk wood. [3][4][5][6][7][8] However, it has also been demonstrated that the spatial distribution of water close to the surface is inhomogeneous. [9][10][11][12] Typically, the MC does not reach a steady state but is continuously responding to changes in environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pieces of environmental legislation have been established or will be introduced throughout Europe. This evolution in combination with the skyrocketing solvent prices, negative trends on the wood market and public concern over the use of tropical wood species have resulted in problems for the European joinery and coating industry (Ahola et al 1999). Although coating systems with reduced pollution output and energy requirements have been available for many years (e.g.…”
Section: Introductionmentioning
confidence: 99%